Author correction: The landscape of genomic alterations across childhood cancers - Gröbner, Susanne; Jones, Barbara Christine; Buchhalter, Ivo; Johann, Pascal-David; Balasubramanian, Gnana Prakash; Bender, Sebastian; Hutter, Barbara; Sturm, Dominik; Pfaff, Elke; Hübschmann, Daniel; Heinold, Michael; Eils, Jürgen; et al. (Nature, 2018)
In this Article, author Benedikt Brors was erroneously associated with affiliation number ‘8’ (Department of Developmental Neurobiology, St Jude Children’s Research Hospital, Memphis, Tennessee, USA); the author’s two other affiliations (affiliations ‘3’ and ‘7’, both at the German Cancer Research Center (DKFZ)) were correct. This has been corrected online.